Comparison of skeletal age with chronological age in thalassemic patients of 9?15 years: Role of growth hormone level - Imtiaz, Humaira; Akbar, Wajid; Javed, Sumaira; Ambreen, Sadaf; Awan, Ayesha Naureen (Pakistan Journal of Physiology, 2019)
Background: Thalassemia major is evident in early childhood causing growth retardation and visceromegaly. The objective of this study was to compare the bone age at 9?15 years in thalassemic children with normal children through growth hormone estimation. Methods: This study was conducted in collaboration with Fatimid Hospital Peshawar and Paediatrics Unit, Khyber Teaching Hospital, Peshawar from Aug 2014 to Jun 2018. The sample size was calculated as 156. After obtaining written informed consent of the parents, blood samples of children were taken for growth hormone assay using commercially available ELIZA kits. Bone age was determined on hand-wrist radiographs by evaluation of ossification centres. Skeletal and chronological ages, and growth hormone level in thalassemic and normal children of same age group were compared. Data was analysed using SPSS-20. Results: In total 156 children 97 (62.2%) were male and 59 (37.8%) were female with mean age 11.9±2.2 years. In thalassemia patients, 49 (62.8%) were male and 29 (37.2%) were female. There were significant differences in bone age between the groups (p=0.0001) as compared to their chronological age. Growth hormone level among children with thalassemia (1.18±0.56 ng/ml) were significantly lower (p=0.025), compared to the control group (5.08±15.02 ng/ml). Bone age was significantly correlated to growth hormone (r=0.244, p=0.031) in thalassemia patients. The correlation between bone age and growth hormone was found non-significant (r=0.161, p=0.302) in control group. Conclusion: Growth hormone level and hand-wrist X-ray should also be used in assessment of thalassemic children for evaluation of possible growth retardation. Pak J Physiol 2019;15(4):49–51